Analysing the impact of a business intelligence system and new conceptualizations of system use - Gonzales, Rolando; Wareham, Jonathan (Universidad ESAN. ESAN Ediciones, 2019)
Purpose – In this study three models were empirically compared the DeLone and McLean model the Seddon model and the Modified Seddon model by measuring the impact of a business intelligence system (BIS) in companies in Peru. After that the mediators and dependent constructs were analysed todetermine if they were behaving properly (a good level of variance explanation and significant relations with others constructs). The study used a sample of 104 users of the BIS from companies in several important economic sectors in a quasi-voluntary context and with six constructs: information quality system quality service quality system dependence (system use) user satisfaction and perceived usefulness (individual impact). Design/methodology/approach – To interpret the results the authors used structural equations. The idea was to look for the best fit and explanations for the outcomes. The main difference in these models is that the DeLone and McLean model considers system dependence (system use) as a part of information system success but in the Seddonmodel it is a consequence of it. Findings – The Seddon model seems to show the best fit and explanation for the outcomes. After that a review of the system use construct was realised because of its limited variance explained and the few significant relations with other constructs to improve its explanation power in future research. Research limitations/implications – It is estimated that the sample includes more than 15 per cent of all the companies that use a BISs in Peru so the size of the sample is adequate but it is not entirely random and therefore limits the generalizability of outcomes. Besides that a sample size that is bigger could be better for the sake of making a more detailed analysis permitting the use of some items with less power or the use of another statistical procedure for structural equations such as the Asymptotical Distribution Free permitting amore detailed analysis (Hair et al. 2006). Originality/value – Business intelligence (BI) one of the most important components of information systems (IS) is playing a very relevant role in business in this time of high competition high amounts of data and new technology. Currently companies feel pressured to respond quickly to change and complicated conditions in the market needing to make the correct tactical operational and strategic decisions (Chugh and Grandhi 2013). BI is one of the most important drivers of the decade (Gartner 2013). Big companies of IS are creating special units specialised in BI helping companies become more efficient and effective in daily operations.

Propósito - En este estudio se compararon empíricamente tres modelos: el modelo DeLone y McLean el Seddon y el Seddon modificado que miden el impacto de un sistema de inteligencia empresarial (BIS) en empresas de Perú. Después de eso los mediadores y los constructos dependientes se analizaron para determinar si se comportaban correctamente (un buen nivel de explicación de la varianza y relaciones significativas con otras construcciones). Diseño/metodología/enfoque - El estudio utilizó una muestra de 104 usuarios de BIS de empresas de varios sectores económicos importantes en un contexto casi voluntario y con seis constructos: calidad de la información calidad del sistema calidad del servicio dependencia del sistema (uso del sistema) satisfacción del usuario y utilidad percibida (impacto individual). Para interpretar los resultados utilizamos ecuaciones estructurales. La idea era buscar el mejor ajuste y explicaciones para los resultados. Hallazgos - La principal diferencia en estos modelos es que el modelo de DeLone y McLean considera la dependencia del sistema (uso del sistema) como parte del éxito del sistema de información pero en el modelo de Seddon es una consecuencia de ello. Este modelo parece mostrar el mejor ajuste y explicación para los resultados. Se realizó una revisión del constructo "uso del sistema" (dependencia del sistema) debido a su limitada variación explicada y las pocas relaciones significativas con otros constructos en este y otros estudios con el fin de mejorar su poder de explicación en futuras investigaciones. Originalidad/valor - Esta investigación es una buena comparación de tres modelos (uno es una variación del segundo) para determinar el mejor de ellos al analizar un sistema de inteligencia empresarial. Los datos son "reales" de 104 ejecutivos de trece empresas peruanas de diferentes sectores económicos. Además se realiza una revisión del constructo "uso del sistema" con el propósito de encontrar alternativas para futuros estudios.
Keywords: DeLone and McLean model; Seddon model; Modelo DeLone y McLean; System use construct; Modelo seddon; Impacto de un sistema de inteligencia empresarial; Impact of a business intelligence system; Constructo "uso del sistema"; https://purl.org/pe-repo/ocde/ford#5.02.04